2020
DOI: 10.1016/j.celrep.2020.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Programs Define Intratumoral Heterogeneity of Ewing Sarcoma at Single-Cell Resolution

Abstract: Highlights d Time-resolved single-cell RNA-seq of EWSR1-FLI1 induction in an Ewing sarcoma cell line d Highly specific transcriptomic signature of EWSR1-FLI1 chimeric oncogene d Sources of transcriptomic heterogeneity in Ewing tumors d Correlations between EWSR1-FLI1 activity and metabolic and other phenotypic states

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 75 publications
9
124
0
Order By: Relevance
“…Multiple studies have demonstrated that ectopic EWSR1-FLI1 expression leads to the expression of neuroectodermal markers in MSCs and that EWSR1-FLI1 depletion in Ewing sarcoma cells leads to increased mesenchymal gene expression patterns [13,14]. Consistent with these findings, our analysis showed that samples with lower EWSR1-FLI1 expression had higher PHATE_1 positions (more mesodermal), and samples with higher EWSR1-FLI1 expression had lower PHATE_1 positions (more pluripotent/neuroectodermal) (Figures 3 and S5).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Multiple studies have demonstrated that ectopic EWSR1-FLI1 expression leads to the expression of neuroectodermal markers in MSCs and that EWSR1-FLI1 depletion in Ewing sarcoma cells leads to increased mesenchymal gene expression patterns [13,14]. Consistent with these findings, our analysis showed that samples with lower EWSR1-FLI1 expression had higher PHATE_1 positions (more mesodermal), and samples with higher EWSR1-FLI1 expression had lower PHATE_1 positions (more pluripotent/neuroectodermal) (Figures 3 and S5).…”
Section: Discussionsupporting
confidence: 84%
“…Recent reports indicate that EWSR1-FLI1 expression levels play a role in defining tumor heterogeneity, particularly in defining proliferative and migratory subpopulations [14,20]. In the above results, we found that EWSR1-FLI1 pushes Ewing sarcoma cells along a developmental trajectory between pluripotent/neuroectodermal and mesodermal cell states.…”
Section: Phate_1 Gene Scores Identify Mesenchymal-like Cellular Subposupporting
confidence: 79%
See 2 more Smart Citations
“…While fluctuations in EWS-FLI1 levels and the ensuing consequences for YAP/TAZ signaling may be the basis for the metastatic potential of a small fraction of tumor cells in Ewing sarcoma (2% according to the postulated biomarker LOX [122]), they may not fully explain Ewing sarcoma aggressiveness. First, while there is a recent single-cell RNA-sequencing-based demonstration of cell-to-cell heterogeneity in EWS-FLI1 RNA levels associated with distinct transcriptional programs [219], direct evidence for variations in EWS-FLI1 protein levels in Ewing sarcoma is still missing. Second, there is evidence for YAP being required for sustained Ewing sarcoma cell proliferation and anchorage-independent growth [131].…”
Section: Yap/taz In Ewing Sarcomamentioning
confidence: 99%